2019
DOI: 10.1002/we.2386
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine main‐bearing loading and wind field characteristics

Abstract: This paper investigates the relationship between wind turbine main‐bearing loads and the characteristics of the incident wind field in which the wind turbine is operating. For a 2‐MW wind turbine model, fully aeroelastic multibody simulations are performed in 3D turbulent wind fields across the wind turbine's operational envelope. Hub loads are extracted and then injected into simplified drivetrain models of three types of main‐bearing configuration. The main‐bearing reaction loads and load ratios from the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 16 publications
1
78
1
Order By: Relevance
“…Hub loadings taken from aeroelastic code are used as inputs to models which represent three-and fourpoint mount systems in order to compare the loads seen by each. The results of this work indicate that radial loads seen by four-point mount systems are generally higher than for the three-point system, but they also saw a corresponding reduction in axial-to-radial load ratios, a quantity for which high values have been associated with potentially damaging events such as unseating of rollers (Hart et al, 2019). Given the reported higher instances of failures in three-point systems in this same work, it is suggested that specific loading combinations (in terms of axial and radial loads) rather than just individual load magnitudes may be important to understanding failures.…”
Section: Multibody Modelsmentioning
confidence: 76%
See 3 more Smart Citations
“…Hub loadings taken from aeroelastic code are used as inputs to models which represent three-and fourpoint mount systems in order to compare the loads seen by each. The results of this work indicate that radial loads seen by four-point mount systems are generally higher than for the three-point system, but they also saw a corresponding reduction in axial-to-radial load ratios, a quantity for which high values have been associated with potentially damaging events such as unseating of rollers (Hart et al, 2019). Given the reported higher instances of failures in three-point systems in this same work, it is suggested that specific loading combinations (in terms of axial and radial loads) rather than just individual load magnitudes may be important to understanding failures.…”
Section: Multibody Modelsmentioning
confidence: 76%
“…In Hart et al (2019) the loading experienced by WTMBs is investigated using simple beam-support representations of the drivetrain 5 . Hub loadings taken from aeroelastic code are used as inputs to models which represent three-and fourpoint mount systems in order to compare the loads seen by each.…”
Section: Multibody Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of analyses which try to understand the loading conditions of MBs in wind turbines (in order to better understand their operational conditions and load characteristsics), detailed model-based investigations are required. Work of this type exists in the literature (Hart et al, 2019b) in which analytical models are used to consider MB loading. This paper considers the validity of simplified analytical drivetrain representations of the type used in these load studies by comparisons with higher fidelity 3D finite element models.…”
mentioning
confidence: 99%